Does Live Streaming Feature Increase Consumer's Trust on Online Shopping? - Iisnawati Iisnawati; Welly Nailis; Islahuddin Daud (Faculty of Economics, Universitas Sriwijaya, 2021)
Live streaming in e-commerce has become the latest trend in the world of online shopping. Live streaming is effective and successful in influencing online shopping decisions in e-commerce, market places and social media, especially in China. The purpose of this study is to empirically prove the influence of live streaming experience to online shopping decisions on social media through trust. The urgency of this research is the phenomenon of a new shopping experience with live streaming on social media which is expected to increase trust for shopping on social media. This study will use primary data by distributing questionnaires to 100 users of the live streaming feature on social media who are domiciled in Palembang with non-probability sampling technique. This study is using Path analysis with SPSS. The results show that the experience of live streaming in online shopping on social media can influence consumers' online shopping decisions through trust.